(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Alopecia areata is a chronic, immune disorder which targets hair follicle epithelium and characterised by hair loss as localised patches. It is a disease that is associated with other auto-immune diseases. This review aims to describe etiopathogenesis, differential diagnosis and treatment of Alopecia. The basic aetiology of Alopecia is the interaction between Human Leukocyte Antigen – DR isotype (HLA-DR) and Human Leukocyte Antigen – DQ isotype (HLA-DQ) on T cells and autoimmunity. The available treatments are limited. The treatments approved by the Food and Drug Administration (FDA) include corticosteroids and anti-inflammatory agents. There is a strong need for developing new pharmacological treatments for alopecia and selected treatments like Janus kinases (JAK) inhibitors therapy is changing the way to treat Alopecia areata.